Changes and challenges in the face of digital disruptions at community print newspapers of Boland Media and WP Media : perspectives from the newsroom - Van der Spuy, Michelle (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.